Water pathways in the bacteriorhodopsin proton pump - Bondar, Ana-Nicoleta; Fischer, Stefan; Smith, Jeremy C. (The journal of membrane biology, 2011)
Internal water molecules play key roles in the functioning of the light-driven bacteriorhodopsin proton pump. Of particular importance is whether during the proton-pumping cycle the critical water molecule w402 can relocate from the extracellular to the cytoplasmic side of the retinal Schiff base. Here, classical mechanical and combined quantum mechanical/molecular mechanical reaction path computations are performed to investigate pathways and energetic factors influencing w402 relocation. Hydrogen bonding between w402 and the negatively charged Asp85 and Asp212 largely opposes repositioning of the water molecule. In contrast, favorable contributions from hydrogen bonding of w402 with the Schiff base and Thr89 and from the untwisting of the retinal polyene chain lower the energetic cost for water relocation. The delicate balance between the competing contributions underlies the need for highly accurate calculations and structural information.
First published online: 28 November 2010
Gesehen am 06.04.2022